Critical mass and voice: Board gender diversity and financial reporting quality. Issue 1 (February 2022) - Dobija, Dorota; Hryckiewicz, Aneta; Zaman, Mahbub; Puławska, Karolina
Abstract: Based on the notion that a diverse board takes a more balanced perspective and pays greater attention to financial reporting oversight, this paper examines the association between board gender diversity and financial reporting quality. Specifically, we study the enablers that allow women to add value to the monitoring activities in the context of limited affirmative actions to promote women on boards. We provide evidence that increased share of women on boards is associated with improved financial reporting quality proxied by reporting timeliness, earnings management, and auditor opinions. We find that in companies that do not have a sufficient number of women on boards, the critical mass effect can be replaced by the "voice" effect, i.e., it is still possible to improve financial reporting quality by having a woman chair the board.